REM genes controlling phyllotaxis and yield: bridging findings from Arabidopsis thaliana to Brassica napus - Ferrario, Carlotta C.; Caselli, Francesca; Davlatboeva, Shokhsanam; Blom, Evert-Jan; van Tunen, Arjen; Gregis, Veronica; Kater, Martin M. (Frontiers in Plant Science, 2026)
One of the main challenges in agriculture is the increasing demand to enhance plant yield per hectare. This is crucial not only for boosting food production to support a growing global population but also for minimizing land use for agricultural purposes. Seed yield is of particular importance since seeds are the primary source of carbohydrates and oil. The number of seeds that develop per plant is influenced by various factors, among which inflorescence architecture is a key trait. The geometrical organization of the inflorescence, known as phyllotaxis, plays an important role during reproductive development across many species. Despite its significance, the molecular mechanisms underlying phyllotactic patterning are still not fully understood. Recently, we demonstrated that the REM genes AtREM34 and AtREM35 are important in establishing phyllotactic patterns in Arabidopsis inflorescences. In this study, we investigated the genetic relationship between these two REM transcription factor genes and a closely related member, AtREM36. Interestingly, we show that double mutants of these genes display an increased number of siliques produced on the main stem. To explore the translational potential of this finding in the economically important seed crop Brassica napus (rapeseed), we identified and functionally analyzed, through complementation tests, a set of homologous BnaREM genes. This application-driven study uncovers novel genes associated with phyllotaxis and yield in the Brassicaceae family, contributing to our understanding of plant architecture and offering insights into sustainable strategies for crop improvement.